Identificación de polifenoles individuales y evaluación de la actividad anticancerigena de la Ligaria cuneifolia (Liga-liga) - Arenas Chávez y Cols., Carlos (2019)
Ligaria cuneifolia (liga-liga) is used in traditional medicine in our country for the treatment of many health disorders, but there is limited information on their pharmacological properties. A methanol extract of Ligaria was prepared and its individual polyphenols were identified by HPLC coupled to mass spectrometry (HPLC / MS) on a Phenomenex Luna C18 column with ultraviolet detection at 280 and 320 nm using an electrospray ionization (ESI). The mobile phase was A: water/ acetic acid 98/2 (v/ v) and B: water / acetonitrile /acetic acid 49.5/50/0.5 with a flow rate of 1mL/min a gradient program. The plant extracts (0-100 mg /mL) were incubated in cell lines for colon cancer (HCT-116), breast (MDA-MB-231), prostate (PC-3), cancer liver (Hep-G2), skin cancer (A-375)and ovarian cancer (OVCAR-3). The total polyphenol content showed a significant amount of bioactive compounds.The Ligaria exhibited concentration-dependent activity in all cancer cell lines. The methanol extract was more active in colon cancer cells (IC50 = 28.14 mg / ml). A variety polyphenols were identified mainly , quercetin, chlorogenic acid, ellagic acid and chlorogenic acid glycoside.